The School Physical Environment, and Its Role in Teachers’ Performance of the First Cycle in Basic Education - A Field Study in Damascus City - العلي شيراز نواف (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aimed to identify the role of the School Physical Environment in Teachers’ Performance of the First Cycle in Basic Education in Damascus City, and identify the differences in means of members answers about role of the School Physical Environment in their Performance according to the variables (years of experience, scientific and educational qualifications). To achieve the object of the research used the descriptive method and a questionnaire has been included (54) items, included two axises, then applied to a sample of (298) Teachers in Damascus City for the academic year 2019/2020. Validity of the questionnaire was established though a jury of (7) specialized of the teaching staff of faculty at Damascus and Tishreen Universities. Also it was confirmed by its application to a survey sample of (36) Teachers by using the Alpha-Cronbach coefficient, which was (0.953) and (0.979) by the Spearman Brown coefficient. The research concluded the following results: The role of the School Physical Environment in Teachers’ Performance of the First Cycle in Basic Education in Damascus City was middle degree. There are no found statistically significant differences between the answers of Teachers of the First Cycle in Basic Education in Damascus City about the role of the School Physical Environment in their Performance according to the variable years of experience. There are found statistically significant differences between the answers of Teachers of the First Cycle in Basic Education in Damascus City about the role of the School Physical Environment in their Performance according to the variable scientific and educational qualifications in favor of the educational qualification diploma. The research recommended intensifying the interest in the school environment and improving it and preparing schools to allow the usage of instructional aids efficiently.